Some solutions for online monitoring the vibration of transformers and the application to identify the state of the transformers - , Truong Tuan Anh; Dao Duy Yen (IJRDO - Journal of Electrical And Electronics Engineering, 2020)
The electrical system is a complex system in both structure and operation. When an incident occurs, any element of the system affects the reliability of electricity supply, electricity quality and causes great damage to economy. The identification the state of transformers in the working process will help us diagnose early the breakdown forms in the 3-phase transformers. This is a necessary work because it will contribute to reduce economic losses and improve the reliability, the quality of electricity supplied to consumers. The paper focuses on research some solutions for online monitoring the vibration of transformers and application to identify the state of the transformers distributaring at 22/0.4kV in normal working condition and in 6 breakdown form.